A verdade do Gato - Hamers, Jeremy (Belgium : Trikolon Productions, 2006)
Burning sugar cane fields, exploited seasonal workers and 'El Gato' (‘The Cat’). He hires the men who harvest sugar cane in the Brazilian village of Carmo do Rio Verde. One single company owns and leases the sugar cane fields and produces ethanol. 1,200 of the 2,000 workers are seasonal. They have to work in humiliating conditions, harvesting the burnt fields in order to produce bioethanol. El Gato promises them good wages and decent accommodation, for which he takes off 4 percent of their pay. The seasonal worker Sebãstiao Soares, is just one of the many workers who come from faraway places in Brazil for the harvest, and becomes a victim of the machinery. The film unveils the human price of Brazil’s cane industry.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films